Perawatan Diri dengan Kualitas Hidup Penderita DM (Comorbid) di Masa Pandemi COVID-19 - Nur Insani; Sri Hartini Harianja; Syirli Anggriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the relationship between self-care for DM sufferers (Comorbid) and their quality of life during the COVID-19 Pandemic. This research method is analytically observational using a cross-sectional design. The results showed that the majority of respondents, 74 people (81.3%), had a good quality of life, and 17 respondents with a percentage of 18.7% had a poor quality of life. The majority of respondents, 66 respondents (72.5%), have adequate self-care, 20 respondents (22.0%) have good self-care, and five respondents (5.5%) are in the less category. P-value = 0.000. In conclusion, good self-care for DM sufferers (comorbid) tends to improve the quality of life for DM patients. Keywords: COVID-19, Diabetes Mellitus, Quality of Life, Self Care